2019
DOI: 10.1177/2053369119875386
|View full text |Cite
|
Sign up to set email alerts
|

There is increasing evidence to suggest that brain inflammation could play a key role in the aetiology of psychiatric illness. Could inflammation be a cause of the premenstrual syndromes PMS and PMDD?

Abstract: The research points to alterations in the function of the GABA-A receptor. GABA (gamma-aminobutyric acid) is an inhibitory neurotransmitter in the central United Kingdom of Great Britain and Northern Ireland

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 52 publications
0
13
0
2
Order By: Relevance
“…A sequence of local and inter-cellular inflammatory interactions in the endometrium occurs in the late luteal phase due to the decline in estradiol and progesterone levels, which have antiinflammatory properties [33]. The magnitude of cyclic changes in inflammatory markers is not the same in all women, and some researchers indicate an essential role of chronic inflammation in PMS etiology [13,14]. One of the proposed hypotheses that seems crucial to fully understand PMS and inflammation's potential connection is altered sensitivity to physiological hormonal fluctuations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A sequence of local and inter-cellular inflammatory interactions in the endometrium occurs in the late luteal phase due to the decline in estradiol and progesterone levels, which have antiinflammatory properties [33]. The magnitude of cyclic changes in inflammatory markers is not the same in all women, and some researchers indicate an essential role of chronic inflammation in PMS etiology [13,14]. One of the proposed hypotheses that seems crucial to fully understand PMS and inflammation's potential connection is altered sensitivity to physiological hormonal fluctuations.…”
Section: Discussionmentioning
confidence: 99%
“…However, chronic inflammation and oxidative stress can lead to many diseases [11], and they are also considered possible factors of PMS development [12,13]. It is known that women of reproductive age experience alternation of inflammation status during the menstrual cycle [14]. Until now, relatively many studies have been conducted in which individual biomarkers of inflammation and oxidative stress were assessed in the PMS context; however, although their results are inconsistent, no literature review has been performed to order and summarize them.…”
Section: Introductionmentioning
confidence: 99%
“…Persistent low estrogen level in the luteal phase may contribute to the vulnerability of the women to emotional symptoms, but not directly to PMDD symptoms. For example, the lower estrogen in the luteal phase might contribute to susceptibility to inflammatory reaction and indirectly support the role of inflammation mechanism in PMDD [25]. However, these claims need to be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thys-Jacobs et al [24] demonstrated a low free luteal estradiol level among women with PMDD. The brain inflammation had been suggested to be a factor contributing to PMDD [25]. The anti-inflammatory effect of estrogen was suggested to play a role in the link between estrogen drop and premenstrual symptoms in the luteal phase.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 – 10 ] Mounting evidence suggests that brain abnormalities, including abnormal brain structure and function and inflammation, may contribute to PMS/PMDD etiology. [ 11 13 ] Moreover, elevated cerebellar gray matter volume, as well as metabolism, has been detailed in PMDD. Additionally, differential corticolimbic stimulation in response to emotional stimuli differentiates the PMDD brain, particularly amplified amygdalar and reduced frontocortical role.…”
Section: Introductionmentioning
confidence: 99%